Emotional Landscapes: Romantic Travels in Scotland. (September 2013) - White, R S
Abstract : This paper compares three Romantic accounts of travel through Scotland: Dorothy Wordsworth's published journal, Recollections of A Tour Made in Scotland A.D. 1803, Coleridge's Notebook entries covering the same journey, as he accompanied Dorothy and William for part of the way, returning alone, and Keats's record of the walking tour he made with Charles Armitage Brown in 1818. The concentration falls on the kinds of emotions the writers felt in response to distance and landscape, which emerge as revealingly different in each case. Some remarks on the emerging discipline of Emotional Geography conclude the essay.